THESAURUS MODELLING OF ENGLISH AND RUSSIAN EDUCATIONAL TERMS - Zhuchkova, Irina (Revista Inclusiones, 2019)
Within the educational discourse of English-speaking countries, there are many concepts that denote various objects and phenomena that do not completely coincide in their meaning with Russian educational terms. As a result, Russian people working in the educational sphere often do not understand the meaning of translated terms and are confused in their use, especially when it comes to terms from different variants of the English language. The current research is aimed at systematizing English and Russian educational discourse and terms within it via thesaurus modelling of terms related to the educational discourse of American and British variants of English and comparing them with Russian terminology. The research showed that systematizing terms via the construction of the English-Russian thesaurus could help not only differenciate the nuances in meaning due to the new thesaurus entries but also illustrate the relations among these terms due to the schemes made for the main terms in the constructed semantic field.